Nuclear receptor crosstalk - defining the mechanisms for therapeutic innovation - De Bosscher, Karolien; Desmet, Sofie J; Clarisse, Dorien; Estébanez-Perpiña, Eva; Brunsveld, Luc (Nature reviews. Endocrinology, 2020)
Nuclear receptor crosstalk can be defined as the interplay between different nuclear receptors or between their overlapping signalling pathways. A subset of nuclear receptors (such as PPARs and RARs) engage in the formation of well-characterized 'typical' heterodimers with RXR. 'Atypical' heterodimers (such as GR with PPARs, or PPAR with ERR) might form a novel class of physical complexes that might be more transient in nature. These heterodimers might harbour strong transcriptional flexibility, with no strict need for DNA binding of both partners. Direct crosstalk could stem from a pairwise physical association between atypical nuclear receptor heterodimers, either via pre-existing interaction pairs or via interactions that are newly induced with small molecules; such crosstalk might constitute an uncharted space to target nuclear receptor physiological and/or pathophysiological actions. In this Review, we discuss the emerging aspects of crosstalk in the nuclear receptor field and present various mechanistic crosstalk modes with examples that support applicability of the atypical heterodimer concept. Stabilization or disruption, in a context-dependent or cell type-dependent manner, of these more transient heterodimers is expected to fuel unprecedented translational approaches to yield novel therapeutic agents to treat major human diseases with higher precision.